Animasi Kartun 2D Berbasis Seni Pertunjukan Tradisi - Sugihartono, Ranang Agung; Murtono, Taufik (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2012)
Indonesian animation lack in using the potential of local culture is the basic reality for this artistic research. The animation creation that refering on the characteristics of traditional performing arts is the focus. This study uses an pratice-based research. Research procedures conducted in two phases, namely analysis and development/implementation. Analysis involves identifying and studing the research object (puppet motion as a reference) and the creation of animated cartoon films. The results of this artistic research showed that a) Elements such shadow puppets (Wayang Kulit) and Wayang Beber typical with their decorative can be applied in character and environment visualization, and provide imaginative effects, b) Movement shadow puppets have a body language that can be used as a reference animated cartoon motion c) the philosophy and meaning in shadow puppets movement is applied to the animated film that can make an animated cartoon has special characteristics and different from Western animation principles, and d) Performance of narrative animation that refers to Dalang’s narratives in shadow puppets making movies more typical Indonesian animation.keyword: film, cartoon, animation, tradition